Pharmacokinetics of propofol nanoemulsion in dogs Farmacocinética do propofol em nanoemulsão em cães - Luiz R.M. (2013)
Propofol nanoemulsion is a new formulation consisting of nanoemulsified systems, characterized by the absence of lipid vehicle. Changes in drug vehicle may alter the pharmacokinetics and result in different distribution and elimination rates of propofol. The aim of this study was to evaluate the pharmacokinetics of a new oil in water propofol nanoemulsion formulation, compared to the traditional lipid emulsion. Six neutered female mixed-breed dogs were used (10.7±1.5kg) in randomized and self control trial with 30 days interval. They received both propofol formulations administered as a bolus dose of 8mg kg-1 followed by 60 minutes continuous infusion at 0.4mg kg-1 min-1 rate. Arterial blood samples were collected just before induction (0), 2, 5, 10, 15, 30, and 60 minutes after the bolus dose, and after the end of the infusion at five, 10, 15, 30, 60, and 90 minutes and 2, 3, 4, 6, 10, and 24 hours. There were no significant differences in the evaluated pharmacokinetics parameters that included volume of distribution, clearance, elimination rate constant, half-life, and distribution constants, demonstrating that propofol nanoemulsion has no pharmacokinetics differences when compared to the traditional formulation.